2011
DOI: 10.1155/2011/356405
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Model for Estimating Global Solar Radiation on Horizontal Surfaces for Selected Cities in the Six Geopolitical Zones in Nigeria

Abstract: This study proposes a temperature-based model of monthly mean daily global solar radiation on horizontal surfaces for selected cities, representing the six geopolitical zones in Nigeria. The modelling was based on linear regression theory and was computed using monthly mean daily data set for minimum and maximum ambient temperatures. The results of three statistical indicators: Mean Bias Error (MBE), Root Mean Square Error (RMSE), andt-statistic (TS), performed on the model along with practical comparison of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…The applicability of Equation (6) was tested by a comparison with the simple temperature-based model previously proposed (Okundamiya and Nzeako 2010). Results showed that Equation (6) compares more favorably with observed data for considered locations in Nigeria (Okundamiya 2014).…”
Section: Okundamiya Modelmentioning
confidence: 98%
See 2 more Smart Citations
“…The applicability of Equation (6) was tested by a comparison with the simple temperature-based model previously proposed (Okundamiya and Nzeako 2010). Results showed that Equation (6) compares more favorably with observed data for considered locations in Nigeria (Okundamiya 2014).…”
Section: Okundamiya Modelmentioning
confidence: 98%
“…In the absence of sunshine data, cloud-based models can be a useful alternative but are sensible to human biasing (Supit and Van Kappel 1998;Badescu 1999). The temperature-based models can be a convenient way if calibrated for a particular location (Hargreaves and Samani 1982;Allen 1997;Chen et al 2004;Okundamiya and Nzeako 2010;Almorox, Hontoria, and Benito 2011). The hybrid-parameter-based model is reported to predict the solar radiation on a horizontal surface with a high degree of accuracy (Supit and Van Kappel 1998;Menges, Ertekin, and Sonmete, 2006), but most of their input parameters are not readily available at most locations of interest (Besharat, Dehghan, and Faghih 2013).…”
Section: Studied Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the place of Babylon city and these constants has a no unit. When we take the climatic inductions on the incidence solar radiation (degree of temperature and the relative of humidity), we will get the following equations [7], [8], [9]: …”
Section: The Effect Of Change In Temperature and Relativity Of Moistnmentioning
confidence: 99%
“…In the absence of these data, one has to rely on available methods of estimation as well as developing new ones. The availability of such data will encourage possible analysis of application and efficient utilization of solar energy in order to control GHC emissions [ [16], [23], [1], [10]]. …”
Section: Introductionmentioning
confidence: 99%